Design Method for Tooth Profile of Harmonic Drive Considering the Spatial Deformation of Flexspline - Shuang Wang; Hao Qiu; Gedong Jiang (Jixie chuandong)
In order to solve the problem that the tooth designed in plane has profile interference under the influence of spatial deformation of the flexspline，a bidirectional conjugate method considering the spatial deformation of the flexspline is proposed. The double-circular-arc tooth profile of circular spline is obtained through conjugate calculating of preset convex circular arc of flexspline at the front and back sections of tooth width. The concave circular arc profile of flexspline is obtained through the reverse conjugate calculating of convex circular arc profile of circular spline at the front section，and is combined with the preset convex arc to make up the tooth profile of flexspline. According to the results of harmonic drive contact simulation based on 3D finite element analysis，it is effective to avoid the profile interference by introducing the space deformation of flexspline into the tooth profile design.